Modeling Maize Canopy Morphology in Response to Increased Plant Density - He, Liang; Sun, Weiwei; Chen, Xiang; Han, Liqi; Li, Jincai; Ma, Yuanshan; Song, Youhong (Frontiers in Plant Science, 2021)
Increased plant density markedly affects canopy morphophysiological activities and crop productivity. This study aims to model maize canopy final morphology under increased interplant competition by revising the functional-structural plant model i.e. ADEL-Maize. A 2-year field experiment was conducted at Mengcheng, Anhui Province, China in 2016 and 2018. A randomised complete block design of five plant densities i.e. 4.5, 6, 7.5, 9 and 15 plants m-2 with three replications was applied using the hybrid Zhengdan 958. Canopy morphology at different plant densities was measured with destructive samplings when maize canopy was fully expanded. The relationship of changes of organ morphology in relation to increase plant density was analysed based on 2016’s data. The ADEL-Maize was first calibrated for the hybrid at 4.5 plants m-2, and then revised by introducing relationships identified, followed by independent validation with 2018 field data. A heatmap visualisation was shown to clearly illustrate the effects of increased plant density on final morphology of laminae, sheaths and internodes. The logarithmic + linear equations were found to fit changes for the organ size versus increased plant density for phytomers excluding ear position or linear equations for the phytomer at ear position based on 2016 field data., The revision was then further tested independently by achieving satisfactory agreements between the simulations and observations in canopy size under different plant densities with 2018 field data. In conclusion, this study has characterised the relationship between canopy morphology and increased interplant competition for use in the ADEL-Maize, and realised the simulations of final size of laminae, sheaths, and internodes as affected by increased plant density, laying a foundation to test an ideotype for maize withstanding high interplant competition.